Mechanics of heart work in the conditions of loss equilibrium. - Syshko D.V; Savina K.D (Kharkov National Pedagogical University, 2011)
The influence of the vestibular loading on the indexes of mechanics of heart at sportsmen is considered. The indexes of mechanics of work of heart were explored at sportsmen at peace and after vestibular loadings. In the experiment 87 sportsmen took part in age 20-25 years. The vestibular loading was designed by the Barani test. The typology features of reaction of the heart-vessels system on the vestibular loadings are set. The got results gave us the possibility to divide inspected into three groups in accordance with the changes of cardiac activity, which took place. Data are got, in relation to optimum phase operation of heart in the conditions of threat of loss of equilibrium.